Evaluation of Functional Brain Connectivity correlated with Power Spectrum Density during Mental Fatigue - Ferreira, Mylena N. R.; Siravenha, Ana Carolina Q.; C. Filho, Iraquitan; Gomes, Bruno D.; Carvalho, Schubert R. (Anais do Symposium on Knowledge Discovery, Mining and Learning (KDMiLe); 2019: Anais do VII Symposium on Knowledge Discovery, Mining and Learning, 2019)
The progressive and gradual escalation of mental fatigue implies specific alterations in both power spectral values and brain connectivity. Detect these variations can improve the understanding of mental fatigue, and lead to identifying sensitive channels to mental state changes and also to identify brain connectivity profiles. This article aims to identify pairs of electrodes that could be used as indicators of mental fatigue based on highly correlated connectivity variations with power spectral values, and also high significance through both normal and fatigue states. In an effort to validate the selected pairs of channels, labeled and unlabeled datasets were subjected to statistical analysis. Our results indicate the concentration of channels in the anterior and posterior brain regions in the left hemisphere, and attenuation of brain connectivity.